1998
DOI: 10.1111/1467-9469.00086
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Leverage and its Applications

Abstract: The generalized leverage of an estimator is de®ned in regression models as a measure of the importance of individual observations. We derive a simple but powerful result, developing an explicit expression for leverage in a general M-estimation problem, of which the maximum likelihood problems are special cases. A variety of applications are considered, most notably to the exponential family non-linear models. The relationship between leverage and local in¯uence is also discussed. Numerical examples are given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
14

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 26 publications
0
57
0
14
Order By: Relevance
“…Next, we shall be concerned with the identification of influential observations and residual analysis. In what follows we shall use the generalized leverage proposed by Wei, Hu and Fung (1998), which is defined as…”
Section: Diagnostic Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we shall be concerned with the identification of influential observations and residual analysis. In what follows we shall use the generalized leverage proposed by Wei, Hu and Fung (1998), which is defined as…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…Let θ be the maximum likelihood estimator of θ, assumed to exist and be unique, and assume that the log-likelihood function has second-order continuous derivatives with respect to θ and y. Wei, Hu and Fung (1998) have shown that the generalized leverage is obtained by evaluating…”
Section: Diagnostic Measuresmentioning
confidence: 99%
“…The main idea behind the concept of leverage (see, for instance, Emerson, Hoaglin and Kempthorne, 1984;St. Laurent and Cook, 1992;Wei, Hu and Fung, 1998) is that of evaluating the influence of y i on its own predicted value. This influence may be well represented by the derivative ∂ŷ i /∂y i that equals h ii in the normal linear case, where h ii is the ith principal diagonal element of the projection matrix H = X(X T X) −1 X T and X is the model matrix.…”
Section: Generalized Leveragementioning
confidence: 99%
“…Laurent and Cook (1992) and Wei et al(1998). Using equation (2.6) of Wei et al (1998) the (n × n) matrix (∂ŷ/∂y) of generalized leverage in univariate elliptical nonlinear regression models may be expressed as…”
Section: Generalized Leveragementioning
confidence: 99%
“…A medida de alavancagem proposta por Wei et al (1998), generaliza a definição de pontos de alavanca usados em modelos de regressão linear múltipla para outros modelos lineares pertencentes a classe dos MLG, sendo desenvolvida a partir dos elementos h ij da matriz H que é conhecida como matriz de projeção ou "matriz chapéu" (H = X(X'X) -1 X'). Supondo que todos os pontos exerçam a mesma influência sobre os valores ajustados, pode-se esperar que os elementos h ii da diagonal da matriz H sejam definidos por w / n, onde w é o somatório dos elementos h ii definido pelos coeficientes dos modelos e n é o número de observações.…”
Section: Critérios De Adequaçãounclassified